Construction and evaluation of DNA vaccine encoding Crimean Congo hemorrhagic fever virus nucleocapsid protein, glycoprotein N-terminal and C-terminal fused with LAMP1 - Hu, Yong-Liang; Zhang, Lian-Qing; Liu, Xiao-Qian; Ye, Wei; Zhao, Yue-Xi; Zhang, Liang; Qiang, Zun-Xian; Zhang, Lin-Xuan; Lei, Ying-Feng; Jiang, Dong-Bo; Cheng, Lin-Feng; Zhang, Fang-Lin (Frontiers in Cellular and Infection Microbiology, 2023)
Crimean-Congo hemorrhagic fever virus (CCHFV) can cause severe hemorrhagic fever in humans and is mainly transmitted by ticks. There is no effective vaccine for Crimean-Congo hemorrhagic fever (CCHF) at present. We developed three DNA vaccines encoding CCHFV nucleocapsid protein (NP), glycoprotein N-terminal (Gn) and C-terminal (Gc) fused with lysosome-associated membrane protein 1 (LAMP1) and assessed their immunogenicity and protective efficacy in a human MHC (HLA-A11/DR1) transgenic mouse model. The mice that were vaccinated three times with pVAX-LAMP1-CCHFV-NP induced balanced Th1 and Th2 responses and could most effectively protect mice from CCHFV transcription and entry-competent virus-like particles (tecVLPs) infection. The mice vaccinated with pVAX-LAMP1-CCHFV-Gc mainly elicited specific anti-Gc and neutralizing antibodies and provided a certain protection from CCHFV tecVLPs infection, but the protective efficacy was less than that of pVAX-LAMP1-CCHFV-NP. The mice vaccinated with pVAX-LAMP1-CCHFV-Gn only elicited specific anti-Gn antibodies and could not provide sufficient protection from CCHFV tecVLPs infection. These results suggest that pVAX-LAMP1-CCHFV-NP would be a potential and powerful candidate vaccine for CCHFV.